Investigation of impact of DC component on breakdown characteristics for different electric fields under composite AC & DC voltage - ORAL, BÜLENT; İSPİRLİ, MEHMET MURAT (WILEY, 2022)
The valve side of the converter in the high-voltage direct current is subjected to mixed voltages such as composite AC & DC voltage. In this study, the effects of the homogeneity of electric field on breakdown voltage were investigated for different +/- DC component amplitudes of the composite voltage. The field efficiency factor was calculated using mean and maximum field strengths for all of them. Variation of breakdown voltage of air was examined under the composite AC & DC voltage for different ratios +/- DC. As one result of the study, the breakdown occurs at the positive half-wave of the AC voltage despite - DC voltage being applied due to positive corona discharge pulses. This breakdown point is named as the polarity change point. The breakdown voltage increases with the decrease of DC voltage component up to polarity change point in nonuniform electric field. In less uniform electric field, the AC breakdown voltage was measured slightly higher than the DC breakdown voltage. In less uniform electric field, as the ratio of the applied AC voltage to DC voltage increases, the breakdown voltage gradually approaches the AC breakdown voltage. This result is similar to the result obtained for the +DC component in non-uniform electric field experiments.
Keywords: PARTIAL DISCHARGE CHARACTERISTICS; EPOXY-RESIN; GROWTH; TREE